2016
DOI: 10.14260/jemds/2016/1191
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and Dexmedetomidine for Day Care Anaesthesia in Paediatric Surgery

Abstract: BACKGROUNDKetamine is one of the commonly used inducing agent for short surgical procedures particularly in paediatric patients. But, its utility has been restricted because of its unwanted sympathomimetic activity even though it has an excellent analgesic property with minimal respiratory depression. Added to this, it is also associated with undesirable postoperative delirium. In the past, several drugs like Midazolam, Propofol were added to ameliorate the side effects of Ketamine. A Combination of Dexmedetom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…27 Yerramilli et al reported that dexmedetomidine ketamine combination provided smooth recovery with one improving the adverse effects of the other, in day case surgeries in pediatrics. 28…”
Section: Discussionmentioning
confidence: 99%
“…27 Yerramilli et al reported that dexmedetomidine ketamine combination provided smooth recovery with one improving the adverse effects of the other, in day case surgeries in pediatrics. 28…”
Section: Discussionmentioning
confidence: 99%